‫تأثير التسيير بالقيمة على رفع كفاءة الاداء المالي للمؤسسة الاقتصادية دراسة حالة عينة من المؤسسة المسعرة في بورصة الجزائر2013-2017‬‬ - إلياس دريسي (My University, 2019)
"The impact of value based management on raising the efficiency of the Financial performance of the economic institution". This study seeks to know the effect of value based management on raising the efficiency of financial performance of the economic institution, Through a theoretical approach to value based management from a financial point of view, Which appear as a modern management approach that makes the value of the engine and the purpose of the management process, The main objective is to maximize shareholder value, And directing each of the institution's objective, Systems, Operations, Stratégies, Analysis techniques, Methods of assessment, And organizational culture, Towards this fundamental objective in line with the creation of value at all levels within the enterprise, Which is an integrated way to drive its performance, For its various operational and strategic practices help improve the efficiency of its financial performance, In order to achieve the objective of the study, a sample was selected including institutions listed on the Algiers Stock Exchange during the period (2013-2017). Where the efficiency of their financial performance was revealed using value-based management indicators, Specifically Economic value added (EVA) and market value added(MVA), This study concluded that the application of this method by educational establishments had a significant defect. They lack a frame of reference in the performance of Management function, Through its accounting profit to assess the efficiency of its financial performance, While it had to rely on economic profit, which takes all the costs of factors of production, Which requires them to adopt effective administrative entrances to increase the chance of success. ................................................... ‬